Implementasi Project Based Learning Dengan Pendekatan STEM Untuk Meningkatkan Kreativitas Berpikir Santri Pada Materi Termodinamika - Aini, Qurotul; Saefullah, Asep; Rostikawati, Diana Ayu (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2025)
This study was conducted to determine how the effect of the implementation of the Project Based Learning (PjBL) model with the STEM approach on improving students' creative thinking skills on the material of the law of thermodynamics, with data collection techniques through pretest, posttest and questionnaire. The STEM approach is believed to be able to stimulate students to be more creative by integrating science, engineering, mathematics, and engineering in the learning process. The sampling technique used was Purposive Sampling, the sample amounted to 30 people who were students of Pondok Pesantren Modern Assa'adah Serang Banten. The analysis method used in this research is Quantitative Data Analysis. The results showed that there was an effect of the PjBL model with the STEM approach on improving the creative thinking skills of students on the material of the law of thermodynamics. The results of the posttest analysis obtained a p-value = 0.002. This shows that the p-value (sig) <0.05, so H0 is rejected. The PjBL model with the STEM approach is proven to improve the creative thinking skills of students on the material of the law of thermodynamics. The average N-gain score of the experimental class (Pjbl STEM Model) is 0.6640 or 66.4%, the minimum N-gain score is 50.00% and the maximum is 94.00%, including the moderately effective category. While the N-gain score of the control group (PBL Model) was 0.3707 or ineffective category of 37.1%, the minimum N-gain score was 11.00% and the maximum was 80.00%. Respondents' perceptions of learning with the Pjbl STEM model are in the good/satisfied category. The results of the average calculation to have the smallest value of 2.93, the largest value of 3.33 and the average value of each item as a whole obtained a value of 3.19 in the range of 3.41-4.20.